Percentage Destabilization Effect of Some West African Medicinal Plants on the Outer Membrane of Various Bacteria Involved in Infectious Diarrhea - DOUGNON, T. VICTORIEN; HOUNSA, Edna; AGBODJENTO, Eric; SINTONDJI, Kevin (My University, 2021)
Previous work stated that Khaya senegalensis, Anacardium ouest L., Pterocarpus erinaceus, Diospyros mespiliformis, Ocimum gratissimum, Manihot esculenta, Vernonia amygdalina Delile, and Daniellia oliveri have a great potential for the fight against infectious diarrhea. However, data on their antibacterial activity on strains of bacteria responsible for infectious diarrhea are not available. This study is aimed at elucidating the mechanism of action of the antibacterial effect of these plants on some bacterial strains responsible for diarrheal infections. The design of the study included first evaluating the degree of sensitivity of Salmonella typhimurium 14028, Escherichia coli ATCC 25922, Shigella spp., and Salmonella spp. strains to aqueous and hydroethanolic extracts of each plant, followed by the determination of minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and antibiotic power (Pa). This screening was completed with the evaluation of the possible mode of action of the extracts by testing the membrane permeability of these bacterial strains. The data collected indicate that the bacterial strains tested were sensitive to the extracts to varying degrees, except Cassia sieberiana DC and Pseudocedrela kotschyi extracts. For the active extracts, inhibition diameters ranged from 18.33mm to 7 mm. With the exception of Escherichia coli, all strains were sensitive to the aqueous and hydroethanolic extracts of Anacardium occidentale. MICs vary between 3.37 and 25 mg/ml. Membrane permeability test data show that all active extracts affect the bacterial strains tested by attacking the stability of their outer membrane. For all active extracts, the high percentage of membrane destabilization of the bacteria is significantly (p < 0:05) better than that of cefixime used as a reference. Thus, it appears that these extracts can destroy Gram-negative bacteria and increase the fluidity and permeability of their cytoplasmic membrane. The knowledge of the mechanism of action of these extracts is an interesting contribution to the fundamental knowledge on the alternative that medicinal plants represent to antibiotics. These extracts can be used in the management of infectious diarrhea
Keywords: Infectious Desease; Destabilization; Bacteria; Medicinal plants